Judeo-Christian tradition as a source of the Quran: A critical evaluation of Margoliouth's assertion - Muhammad, Akilu Aliyu; Abdul Rahim, Adibah (University of Malaya, 2016)
The assertion that Prophet MuÍammad (p.b.u.h) sourced the Qur’Én from Judeo-Christian tradition is one of the oldest claims promoted by the medieval Christian missionaries. Although there are no concrete, conclusive and irrefutable proofs on such a claim, almost all Christian scholars even the most learned ones subscribed to it and held it to be true. The claim also gets back up in Margoliouth’s treatises on the sources of the Qur’Én. Its reproduction in the work of such an able contemporary Christian scholar may confirm the assertion that the claim still has relevance in the contemporary Christians’ works on Islam. Thus, this research attempts to critically analyse and evaluate Margoliouth’s deliberation on this issue. In an effort to carry out this task, the research attempts to answer some questions such as: did the Prophet (p.b.u.h) really copy or pick up from Biblical traditions? What ware the possible avenues through which he might have picked up such traditions? Based on these questions, the researchers, while applying historical, analytical, evaluative and comparative approaches attempt to critically analyse and investigate Margoliouth’s claim that the Prophet (p.b.u.h) copied from Biblical traditions and the possible chances through which he might have come into contact with those traditions.